Clear-cut terms and culture-sensitive characteristics of distinctive casual sexual relationships in Portuguese emerging adults - Alvarez, Maria-João (2021)
Casual sexual relationships (CSR) are increasingly common but limited empirical research has addressed their terminology and distinctive characteristics. This study sought to identify the most clear-cut terms and to consider how culture-sensitive characteristics distinguish casual sexual relationships among Portuguese emerging adults (N = 262, 18-29 years old). We combined two qualitative studies – one by association and another by free recall – to ascertain the clarity of the terms, plus a quantitative study to further characterize and differentiate them. Participants were asked to match descriptions of CSRs with the respective terms by which they are known (Study 1). The same was investigated using an evocation task requesting that participants produce the terms by which the described CSRs are known (Study 2). Binary logistic regressions were performed to analyze the associations between encounters and labels chosen, taking the effect of gender and age into account. In the third study, participants rated the degree to which eight characteristics were present in the types of CSR, a simultaneous task that led to greater understanding of their descriptive and differentiating characteristics. Multivariate analysis of variance was used, with gender and age as covariates. We conclude that two types of CSR – friends with benefits and one-night stand – and, to a lesser extent, making out, are understood and associated with consensual labels, also found by free-recall. These CSRs proved to be distinct, as they are understood as more different than similar in a set of psychoemotional, behavioral, and sexual characteristics.